Lymphocyte-C-reactive Protein Ratio as Promising New Marker for Predicting Surgical and Oncological Outcomes in Colorectal Cancer. Issue 2 (August 2020) - Okugawa, Yoshinaga; Toiyama, Yuji; Yamamoto, Akira; Shigemori, Tsunehiko; Ide, Shozo; Kitajima, Takahito; Fujikawa, Hiroyuki; Yasuda, Hiromi; Hiro, Junichiro; Yoshiyama, Shigeyuki; Yokoe, Takeshi; Saigusa, Susumu; et al.
Abstract : Background: Systemic inflammation via host-tumor interactions is currently recognized as a hallmark of cancer. The aim of this study was to evaluate the prognostic value of various combinations of inflammatory factors using preoperative blood, and to assess the clinical significance of our newly developed inflammatory score in colorectal cancer (CRC) patients. Method: In total 477 CRC patients from the discovery and validation cohorts were enrolled in this study. We assessed the predictive impact for recurrence using a combination of nine inflammatory markers in the discovery set, and focused on lymphocyte-C-reactive protein ratio (LCR) to elucidate its prognostic and predictive value for peri-operative risk in both cohorts. Results: A combination of lymphocytic count along with C-reactive protein levels demonstrated the highest correlation with recurrence compared with other parameters in CRC patients. Lower levels of preoperative LCR significantly correlated with undifferentiated histology, advanced T stage, presence of lymph node metastasis, distant metastasis, and advanced stage classification. Decreased preoperative LCR (using an optimal cut-off threshold of 6000) was an independent prognostic factor for both disease-free survival and overall survival, and emerged as an independent risk factor for postoperative complications and surgical-site infections in CRC patients. Finally, we assessed the clinical feasibility of LCR in an independent validation cohort, and confirmed that decreased preoperative LCR was an independent prognostic factor for both disease-free survival and overall survival, and was an independent predictor for postoperative complications and surgical-site infections in CRC patients. Conclusion: Preoperative LCR is a useful marker for perioperative and postoperative management of CRC patients. Abstract : Supplemental Digital Content is available in the text